Effect of Categorizing EFL Shaqra University Students’ Writing Errors on Writing Improvement - Majzoub, Islam (Technium Social Sciences Journal, 2021)
This paper aims at using a strategy of categorizing EFL Shaqra University students’ writing errors and identifying its effect in improving students’ writing. The study hypothesized that categorizing students’ errors into main headings related to the types of error, frequencies of error, examples of errors, and causes of errors will provide precise insight into the nature of students’ errors. Moreover, providing students with models to read and extract the difficult vocabularies from them, understanding their meanings, and using them in their writing will improve students’ writing. Hence, the researcher gave 65 female students a title to write about in lecture number one as a pre-test. The title was "women driving in Saudi Arabia", and in lecture number eleven, she gave them a post-tester in the same title after applying the hypothesized teaching strategy. The findings of students’ essay analysis in the pre-test proved that students had many grammatical and lexical mistakes but in the post-test the students writing improved significantly in terms of style, diction, developing ideas, spelling, and punctuation. Even their errors decreased from 936 errors in the pre-test to 57 errors in the post-test which indicates the success of the teaching strategy adopted by the researcher. Accordingly, the researcher recommended that: firstly, instructors should categorize their students’ writing errors to have a clear insight into the nature of their students’ errors hence specifying much time in explaining the areas of students’ weaknesses. Secondly, instructors should provide students with a well-written model to read; and then ask them to criticize those reading models. The students will learn through criticizing and imitating the style of reading models. Moreover, the instructors of Shaqraa should specify much time explaining morphology since it was the branch that the students make many errors in it.